2013
DOI: 10.1089/scd.2012.0605
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Downregulate Articular Chondrocyte Differentiation in Noncontact Coculture Systems: Implications in Cartilage Tissue Regeneration

Abstract: While chondrogenesis of mesenchymal stem cells (MSCs) in vitro has been extensively studied, their participation in cartilage tissue repair remains unresolved. This study was designed to elucidate if MSCs affect the phenotype of articular chondrocytes (ACs). A combination of noncontact coculture modes was developed. Human or rabbit MSCs and rabbit ACs (rACs) were encapsulated in alginate hydrogel beads [three-dimensional (3D)] or cultured in a monolayer [two-dimensional (2D)] and subsequently cocultured in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 53 publications
4
34
0
Order By: Relevance
“…Combined with our observations that blockade of FGF-1 activity either by inhibitors of FGFRsignaling or by a neutralizing antibody inhibited hPCs proliferation in co-culture pellets and that neutralizing antibodies blocked hPCs proliferation induced by MSC CM, our study identifies FGF-1 as the MSC secreted factor that is responsible for the stimulation of hPCs proliferation in cocultures. Even though our data suggested a positive role of FGF-1 in co-culture pellets, recombinant protein may not be good to replace MSCs in the co-culture system, as secreted factors from MSCs may decrease the deposition of the cartilaginous ECM, including GAGs and collagen type II from articular chondrocytes in a long-term culture [48]. Based on our previous studies, we believe that cell-cell contact between MSCs and chondrocytes in the co-culture system is crucial for maintaining chondrogenic phenotypes.…”
Section: Discussionmentioning
confidence: 64%
“…Combined with our observations that blockade of FGF-1 activity either by inhibitors of FGFRsignaling or by a neutralizing antibody inhibited hPCs proliferation in co-culture pellets and that neutralizing antibodies blocked hPCs proliferation induced by MSC CM, our study identifies FGF-1 as the MSC secreted factor that is responsible for the stimulation of hPCs proliferation in cocultures. Even though our data suggested a positive role of FGF-1 in co-culture pellets, recombinant protein may not be good to replace MSCs in the co-culture system, as secreted factors from MSCs may decrease the deposition of the cartilaginous ECM, including GAGs and collagen type II from articular chondrocytes in a long-term culture [48]. Based on our previous studies, we believe that cell-cell contact between MSCs and chondrocytes in the co-culture system is crucial for maintaining chondrogenic phenotypes.…”
Section: Discussionmentioning
confidence: 64%
“…Aung et al (2011) reported that a co-culture of hBMSCs and chondrocytes without cell-cell contact encouraged the expression level of aggrecan mRNA in hBMSCs. Xu et al (2013) showed that the expression of aggrecan mRNA in chondrocytes was inhibited in an indirect co-culture system. The result of the indirect co-culture system we obtained was consistent with their findings.…”
Section: Discussionmentioning
confidence: 99%
“…Total mRNA (up to 2.5 μg) was reverse-transcribed into cDNA using SuperScript® VILO™ Master Mix. cDNA was ampli ied with the TaqMan® Gene Expression Master Mix (Applied Biosystems by Life Technologies, Grand Island, NY, USA) on an ABI 7900HT Sequence Detection System (Applied Biosystems) and probes speci ic for GAPDH, a housekeeping gene that has served as a baseline in several studies on chondrocyteprogenitor interaction and MSC-chondrocyte co-culture [32][33][34][35][36][37], sex-determining region Y (SRY)-box 9 (SOX9), ACAN, Lubricin, Col XI, Col X, VEGF-A, Col I, alkaline phosphatase (ALP), and osterix were used. Known primer sequences for these species appear in Table 1, and where primer sequences are proprietary, the company name and catalogue number are given.…”
Section: Rna Isolation and Analysismentioning
confidence: 99%